Fusion and Breakup Reactions of 17S + 208Pb and 15C + 232ThHalo Nuclei Systems (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this study the calculations of the total fusion reaction cross section have been performed for fusion reaction systems 17F + 208Pb and 15C + 232Th which involving halo nuclei by using a semiclassical approach.The semiclassical treatment is comprising the WKB approximation to describe the relative motion between target and projectile nuclei, and Continuum Discretized Coupled Channel (CDCC) method to describe the intrinsic motion for both target and projectile nuclei. For the same of comparsion a full quantum mechanical clacualtions have been preforemd using the (CCFULL) code. Our theorticalrestuls are compared with the full quantum mechaincialcalcuations and with the recent experimental data for the total fusion reaction  checking the stability of the distancesThe coupled channel calculations of the total fusion cross section Ïƒfus, and the fusion barrier distribution Dfus. The comparsion with experiment proves that the semiclassiacl approach adopted in the present work reproduce the experimental data better that the full quantal mechanical calcautions.